PMM.69 The role of continuous audit in monitoring care for women with diabetes in pregnancy; 4 years experience in a high-risk London unit. (9th June 2014) - Currie, JLD; Black, B; Mustapha, A; Settle, N; Brownhill, H; Kinghorn, I; Needham, J; Anderson, J; Dolan, M; Chambers, A; Dorman, E; Erskine, KJ; et al.
Abstract : Background: Diabetes in pregnancy is managed in the UK by a multidisciplinary team of diabetologists, obstetricians and dietitians, specialist nurses and midwives. Audits were carried out to ensure compliance with guidelines and monitor outcomes. Method: Annual retrospective audit of women with pre-existing and gestational diabetes in pregnancy at a tertiary London hospital (2009–2013). Results: 116 women with pre-existing diabetes were identified. The local distribution of pre-existing diabetes is reversed compared to the UK trend, with a "Type 2" majority of 70%. The majority of pre-existing diabetics were in the older age groups. Overall antenatal care reached national standards with early antenatal booking and timely investigations. The caesarean section rate was 70%, half of which were elective. In patients who were induced 60% had a caesarean section. There was one miscarriage at 20/40 in a T1 and a late stillbirth in a T2 patient. 178 women with gestational diabetes (GDM) were identified. These were younger than pre-existing diabetics. 44% booked for antenatal care after 12 weeks gestation. 63% had a caesarean section. More babies were macrosomic than pre-existing diabetics (13% >4kg compared with 6%). There were two stillbirths, one related to poor diabetic control. There was one shoulder dystocia in a patient diagnosed at 33/40. Conclusion: In general, care for women with pre-existing diabetes and gestational diabetes is of a high standard. However, both conditions are high risk requiring continued surveillance throughout pregnancy. Timely diagnosis and glycaemic control are critical to good outcomes for gestational diabetics. Local audit data aids patient counselling.